1992
DOI: 10.1203/00006450-199205000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin and Hypoxia-Induced Intestinal Necrosis in Rats: The Role of Platelet Activating Factor

Abstract: ABSTRACT. We have previously shown that intravascular platelet activating factor (PAF) causes ischemic bowel necrosis in rats morphologically similar to neonatal necrotizing enterocolitis (NEC). Because endotoxin (LPS) and hypoxia are risk factors for NEC, we studied their effect on PAF metabolism and the development of intestinal injury. Young male Sprague-Dawley rats were anesthetized with pentobarbital and divided into six experimental groups: 1 ) control, 2) LPS alone (2 mglkg), 3) hypoxia alone (5% 04, 4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 14 publications
2
46
0
1
Order By: Relevance
“…Platelet activating factor (PAF) is implicated in the gastrointestinal pathology of NEC. [9][10][11][12] PAF is an inflammatory, phospholipid cytokine contributing to the bowel necrosis seen in experimental NEC. 9 Compared to adults, neonatal gastrointestinal tissue has a relatively greater capacity for producing PAF.…”
Section: Pathophysiology Of Thrombocytopeniamentioning
confidence: 99%
See 1 more Smart Citation
“…Platelet activating factor (PAF) is implicated in the gastrointestinal pathology of NEC. [9][10][11][12] PAF is an inflammatory, phospholipid cytokine contributing to the bowel necrosis seen in experimental NEC. 9 Compared to adults, neonatal gastrointestinal tissue has a relatively greater capacity for producing PAF.…”
Section: Pathophysiology Of Thrombocytopeniamentioning
confidence: 99%
“…14,15 In rats, experimental NEC is prevented by concurrent administration of exogenous PAF-acetylhydrolase 11 or PAF receptor antagonists. 9,10 Although PAF universally stimulates platelet activation, no rat or human studies reported simultaneous PAF and peripheral platelet counts. However, experimental LPS administration to human volunteers results in a rapid fall in platelet counts.…”
Section: Pathophysiology Of Thrombocytopeniamentioning
confidence: 99%
“…5 However, the value of CRP measurement for therapeutic decision making or assessment of prognosis remains uncertain. Other analyses that have been described in infants with NEC include procalcitonin, interleukins and platelet-activating factor, 6,7 but their clinical usefulness has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] Although the hepatic effects of PAF are not completely understood, it has been documented that intravascular administration of PAF can induce an ischemic bowel necrosis similar to that observed in neonatal necrotizing enterocolitis and that PAF mediates the development of endotoxin-and hypoxiainduced intestinal necrosis in rats. [13][14][15] In contrast, recombinant PAF-AH prevented the development of ischemia-elicited necrosis of the duodenum, jejunum, and ileum after injection of PAF into rat descending aorta. 16,17 PAF and PAF-AH are implicated in the pathogenesis of liver and inflammatory bowel diseases in humans including patients with cirrhosis of the liver and Crohn' s disease.…”
mentioning
confidence: 99%